MucR, a Novel Membrane-Associated Regulator of Alginate Biosynthesis in Pseudomonas aeruginosa - Hay, Iain D. (American Society for Microbiology (ASM), 2009)
Alginate biosynthesis by Pseudomonas aeruginosa was shown to be regulated by the intracellular second messenger bis-(3′-5′)-cyclic-dimeric-GMP (c-di-GMP), and binding of c-di-GMP to the membrane protein Alg44 was required for alginate production. In this study, PA1727, a c-di-GMP-synthesizing enzyme was functionally analyzed and identified to be involved in regulation of alginate production. Deletion of the PA1727 gene in the mucoid alginate-overproducing P. aeruginosa strain PDO300 resulted in a nonmucoid phenotype and an about 38-fold decrease in alginate production; thus, this gene is designated mucR. The mucoid alginate-overproducing phenotype was restored by introducing the mucR gene into the isogenic ΔmucR mutant. Moreover, transfer of the MucR-encoding plasmid into strain PDO300 led to an about sevenfold increase in alginate production, wrinkly colony morphology, increased pellicle formation, auto-aggregation, and the formation of highly structured biofilms as well as the inhibition of swarming motility. Outer membrane protein profile analysis showed that overproduction of MucR mediates a strong reduction in the copy number of FliC (flagellin), required for flagellum-mediated motility. Translational reporter enzyme fusions with LacZ and PhoA suggested that MucR is located in the cytoplasmic membrane with a cytosolic C terminus. Deletion of the proposed C-terminal GGDEF domain abolished MucR function. MucR was purified and identified using tryptic peptide fingerprinting and matrix-assisted laser desorption ionization-time of flight mass spectrometry. Overall, experimental evidence was provided suggesting that MucR specifically regulates alginate biosynthesis by activation of alginate production through generation of a localized c-di-GMP pool in the vicinity of Alg44.